KEPEMIMPINAN BERBASIS NILAI DAN DUKUNGAN EMOSIONAL: REFLEKSI KUALITATIF ATAS LOYALITAS KARYAWAN DALAM PERSPEKTIF INTERPERSONAL - Ruben Simangunsong; Kornel Munthe; Pandapotan Sitompul; Mawar Nauli; Oyke Alfons Depari (CV. Lafadz Jaya, 2025)
This study aims to examine the relationship between values-based leadership and emotional support on employee loyalty in the context of interpersonal relationships in the workplace. Using a qualitative approach based on literature, this study reflects on how employees' interpersonal experiences contribute to the formation of emotional and sustainable loyalty. The results of the study indicate that employees interpret leadership not only as a structural function but also as a form of human relations built on values such as honesty, empathy, and appreciation. Emotional support from leaders—manifested through attention, recognition, and presence in critical situations—plays a crucial role in creating a sense of security and psychological attachment to the organization. Interpersonal experiences such as open communication, fair treatment, and trust are key factors in shaping employee loyalty that goes beyond material incentives. The main conclusion of this study is that values-based leadership and emotional support complement each other in building authentic and meaningful loyalty. This study recommends strengthening the emotional and value dimensions in modern organizational leadership practices.